Sorghum (Sorghum bicolour (L.) Moench) growth and development features under the influence of growth regulator - Liudmyla Pravdyva; Oleg Prysiazhniuk; Valerii Khakhula; Lesia Kachan; Taras Panchenko (Наукові горизонти, 2023)
There has been a growing interest in growing sorghum (Sorghum bicolor L. (Moenh) as a bioenergy crop, as it can be used to produce biofuels (ethyl alcohol) and solid fuels (pellets and briquettes from the above-ground mass). Sorghum grain is characterised by a high starch content of up to 80%. The research topic is relevant but poorly understood. The research aims to study the effect of growth regulators on the growth and development of sorghum in the conditions of the Right-Bank Forest-Steppe of Ukraine. The following research methods were used: field, measuring and weighing, mathematical and statistical. The study presents the results of research for 2016-2019, where the influence of elements of cultivation technology on the peculiarities of the formation of biometric parameters was studied. plant growth regulator had an impact on field germination, vegetation period, biometric indicators of plant growth, and leaf area. The closeness of the correlations of the studied indicators was established, and a correlation-regression analysis of the data was carried out, which showed a strong correlation between the growing season and plant height, where the coefficient was R=0.9264, and the coefficient of determination R2 =0.9864. There was also a strong relationship between stem diameter and plant height, where the correlation coefficient was R=0.9767 and the coefficient of determination was R2 =0.954. The conducted studies confirm the feasibility of using a growth regulator that improves plant development and will contribute to increasing the yield and quality of grain and biomass of sorghum. The obtained results of the research give grounds to believe that growth regulators contribute to the production of environmentally friendly products and are components of environmentally friendly and energysaving cultivation technology